2008
DOI: 10.1002/pssb.200879607
|View full text |Cite
|
Sign up to set email alerts
|

Novel carbon nanotube network deposition technique for electronic device fabrication

Abstract: We present a novel dry and room‐temperature method for the deposition of random carbon nanotube networks (CNTNs) onto various substrates. This method is based on natural charging of carbon nanotube (CNT) bundles in the gas‐phase and their efficient deposition directly downstream of the synthesis reactor by means of an electric field. The density of the deposited CNTNs was controllably adjusted by varying the deposition time and the electric field strength. Application of this deposition technique for the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The product consisted mainly of small bundles of high quality SWCNTs with a mean diameter of around 1.5 nm and average bundle length 3 μm (supplementary data, figure S1 available at stacks.iop.org/Nano/22/065303/ mmedia). The deposition was performed by means of an electrostatic precipitator (supplementary data, figure S2 available at stacks.iop.org/Nano/22/065303/mmedia), where the density of the collected network was defined by the deposition time and the applied electric field, as described in details elsewhere [5,6]. Controllable positioning of the CNTs at the desired areas during the deposition was achieved by using a shadow mask located at a certain distance from the substrate surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The product consisted mainly of small bundles of high quality SWCNTs with a mean diameter of around 1.5 nm and average bundle length 3 μm (supplementary data, figure S1 available at stacks.iop.org/Nano/22/065303/ mmedia). The deposition was performed by means of an electrostatic precipitator (supplementary data, figure S2 available at stacks.iop.org/Nano/22/065303/mmedia), where the density of the collected network was defined by the deposition time and the applied electric field, as described in details elsewhere [5,6]. Controllable positioning of the CNTs at the desired areas during the deposition was achieved by using a shadow mask located at a certain distance from the substrate surface.…”
Section: Resultsmentioning
confidence: 99%
“…The charging was explained in the framework of aggregation processes leading to the energy release due to the minimization of the surface energy and emission of electrons and positive adsorbent molecules, as described in detail elsewhere [28]. We utilized this phenomenon to increase the deposition efficiency of SWCNT bundles onto the substrate by applying an electric field [5,6], and here the use of a shadow mask allowed us to control the lateral positioning of CNTs during the gas phase deposition. At the initial stages of the deposition process, charged SWCNT bundles are uniformly distributed through the mask opening with the density still below the percolation limit.…”
Section: Cntn Patterned Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…While short parts of a disorganized bundle can easily be metallic, longer ones should have semi-conducting parts in between metallic ones, as will be discussed below. Recently, such bundles have been used to produce thin-film transistors [20,21] illustrating the need for modeling them while so far a theoretical description of these carbon nanotube bundle networks (CNTBN) has been missing. Here, we study such CNTBNs theoretically using Monte Carlo simulations of two-dimensional stick networks similar to many CNTN studies, as e.g.…”
mentioning
confidence: 99%
“…Bundle model. -Zavodchikova et al demonstrated thin-film transistors produced with a direct deposition of aerosol synthesized carbon nanotubes [20,21]. These CNTs aggregate during synthesis forming disorganized bundles of two to seven CNTs in parallel, typically 1 .…”
mentioning
confidence: 99%